EFEKTIFITAS MODEL PEMBELAJARAN MAKE A MATCH DAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA - cahyati cahyati; hudaya latuconsina; estu niana syamiya (Universitas Islam Syekh Yusuf, 2020)
The social studies learning process tends to be teacher-centered learning or teaching staff. The use of the lecture or teacher-centered method tends to make students bored or bored and not motivated to be active in learning activities because during learning the teacher gives many lectures to pursue material attainment. The purpose of this study 1. To analyze the learning model currently used in the learning process 2. To analyze and diagnose factors that cause the learning process to be less than optimal 3. To analyze whether there is a positive and significant effectiveness between the make a match and audio-visual learning model on learning outcomes. This research method uses descriptive quantitative method approach. The regression estimation value shows that the value of t-count = -0.254> t-table = -1.6575 or the p value is sig. = 0.008 <0.05, so it can be concluded that Ha is accepted and H0 is rejected. This means that there is a negative effect of the make a match method on student learning outcomes. The value of the regression estimation shows that the value of t-count = 10.682> t-table = 1.6575 or p value sig. = 0.000 <0.05, so it can be concluded that Ha is accepted and H0 is rejected. This means that there is a significant effect of audio visual on student learning outcomes. The regression estimation results show that the P value is 0.000 <0.05. So it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a significant influence jointly between the make a match method and the audio visual on student learning outcomes. This means that the make a match method has no effect on learning outcomes without the help of other media, audio-visual media has a positive effect on learning outcomes, the make a match method and audio-visual media together have a positive influence on student learning outcomes so that student learning outcomes increase. of the minimum completeness criteria value. Keyword: The effectiveness of the make a match method and audio visual media on learning outcomes.